2017
DOI: 10.1371/journal.pone.0178515
|View full text |Cite
|
Sign up to set email alerts
|

The four-transmembrane protein MAL2 and tumor protein D52 (TPD52) are highly expressed in colorectal cancer and correlated with poor prognosis

Abstract: The four-transmembrane protein MAL2 and tumor protein D52 (TPD52) have been shown to be involved in tumorigenesis of various cancers. However, their roles in colorectal cancer (CRC) remain unclear. In this study, we explored the expressions of MAL2 and TPD52 in tumor specimens resected from 123 CRC patients and the prognostic values of the two proteins in CRC. Immunohistochemical analyses showed that MAL2 (P<0.001) and TPD52 (P<0.001) were significantly highly expressed in primary carcinoma tissues compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…TPD52 is a tumor-promoting gene and is frequently overexpressed in multiple cancers, such as ovarian cancer, 37 prostate cancer, 38 colorectal cancer. 39 Due to the oncogenic role of TPD52 in many cancers, TPD52 should be further studied. Moreover, accumulating evidence revealed that TPD52 was involved in cellular transformation, proliferation, apoptosis, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…TPD52 is a tumor-promoting gene and is frequently overexpressed in multiple cancers, such as ovarian cancer, 37 prostate cancer, 38 colorectal cancer. 39 Due to the oncogenic role of TPD52 in many cancers, TPD52 should be further studied. Moreover, accumulating evidence revealed that TPD52 was involved in cellular transformation, proliferation, apoptosis, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In that time, we have determined that the 19 kDa tetraspanning integral membrane protein, MAL2, is an important regulator of hepatic polarized protein sorting and have shown that it functions in basolateral secretion, basolateral membrane protein delivery and basolateral-to-apical transcytosis [3,4], but what is important to these studies is the finding that MAL2 expression is highly up-regulated up to 100-fold in a host of human cancers, including renal cell carcinoma, mesothelioma, neuroblastoma, cholangiocarcinoma, and cancers of the colon, liver, stomach, breast, ovary and pancreas [5][6][7][8][9][10][11][12][13][14]. High MAL2 expression has also been linked to bad prognosis in patients with colorectal or pancreatic cancer [5,13]. Genomic instability gains in chromosome 8q24 (where MAL2 resides) are associated with several epithelial cell-derived human cancers [15] and likely explains enhanced MAL2 transcript expression in at least a subset of these cancers.…”
Section: Introductionmentioning
confidence: 99%
“…TPD52 is a coiled-coil motif-bearing protein that plays a regulatory role in tumor progression. Previous studies have shown the upregulated expression of TPD52 and its function as a tumor promoter in prostate cancer, 33 colorectal cancer, 34 lung squamous cell carcinoma, 35 and breast cancer. 24 Dasari et al 33 showed that TPD52 overexpression promotes the migration and proliferation of prostate cancer cells, while Kumamoto et al 35 revealed the suppressive effect of TPD52 knockdown on the migration and invasion of lung squamous cell carcinoma cells.…”
Section: Discussionmentioning
confidence: 97%